2022
DOI: 10.1093/jtm/taac036
|View full text |Cite
|
Sign up to set email alerts
|

Similar effectiveness of the inactivated vaccine BBIBP-CorV (Sinopharm) and the mRNA vaccine BNT162b2 (Pfizer-BioNTech) against COVID-19 related hospitalizations during the Delta outbreak in the UAE

Abstract: Inactivated vaccine BBIBP-CorV (Sinopharm; 95% (95%CI: 94%,97%)) and the mRNA vaccine BNT162b2 (Pfizer-BioNTech; 98% (95%CI: 86%,99%)) demonstrated protection against COVID-19 related hospitalizations from the Delta (B.1.617.2) variant. Ongoing efforts are necessary to target vaccine hesitancy and promote booster shots for protection against severe COVID-19 disease and arising variants of concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 6 publications
2
20
0
Order By: Relevance
“…A recent prospective study from the United States reported similar, 85% effectiveness of mRNA vaccines against Covid-19 related hospitalization among patients infected with the Delta or Alpha SARS-CoV-2 variant after two doses (17). In a study conducted in the United Arab Emirates (UAE), the Sinopharm and Pfizer-BioNTech vaccines provided 95% and 98% effectiveness against Covid-19 related hospitalization in patients infected with the Delta variant, respectively (19). We found high protection against mortality of Pfizer-BioNTech, Moderna, Sputnik-V, and AstraZeneca vaccines but lower than 60% effectiveness for the Janssen and Sinopharm vaccines during the Delta wave in these age groups.…”
Section: Discussionmentioning
confidence: 97%
“…A recent prospective study from the United States reported similar, 85% effectiveness of mRNA vaccines against Covid-19 related hospitalization among patients infected with the Delta or Alpha SARS-CoV-2 variant after two doses (17). In a study conducted in the United Arab Emirates (UAE), the Sinopharm and Pfizer-BioNTech vaccines provided 95% and 98% effectiveness against Covid-19 related hospitalization in patients infected with the Delta variant, respectively (19). We found high protection against mortality of Pfizer-BioNTech, Moderna, Sputnik-V, and AstraZeneca vaccines but lower than 60% effectiveness for the Janssen and Sinopharm vaccines during the Delta wave in these age groups.…”
Section: Discussionmentioning
confidence: 97%
“…The study conducted in Guangzhou city of China similarly indicated that the vaccine effectiveness for the two-dose vaccination was estimated to be 59.0% (95% CI 16.0% to 81.6%) against SARS-CoV-2, and 70.2% (95% CI 29.6% to 89.3%) against moderate illness caused by the Delta variant, even though it did not report stratified effectiveness between BBIBP-CorV and CoronaVac [23], which was reported in Zhengzhou city of China [24]. One study conducted in the United Arab Emirates also indicated that the inactivated vaccine BBIBP-CorV and the mRNA vaccine BNT162b2 demonstrated protection against COVID-19-related hospitalizations caused by the Delta variant with 95% (95% CI 94% to 97%) and 98% (95% CI 86% to 99%) effectiveness, respectively [25].…”
Section: Effectiveness Within the Real-environmentmentioning
confidence: 95%
“…A recent prospective study from the United States reported similar, 85% effectiveness of mRNA vaccines against Covid-19 related hospitalization among patients infected with the Delta or Alpha SARS-CoV-2 variant after two doses (20). In a study conducted in the United Arab Emirates (UAE), the Sinopharm and Pfizer-BioNTech vaccines provided 95% and 98% effectiveness against Covid-19 related hospitalization in patients infected with the Delta variant, respectively (22). We found high protection against mortality of Pfizer-BioNTech, Moderna, Sputnik-V, and AstraZeneca vaccines but lower than 60% effectiveness for the Janssen and Sinopharm vaccines during the Delta wave in these age groups.…”
Section: Discussionmentioning
confidence: 99%